Psammobatis extenta, Zipper Sandskate - Pollom, R. (2020)
The Zipper Sandskate (Psammobatis extenta) is a small (to 35 cm total length) skate that occurs in the Southwest Atlantic from Rio de Janeiro, Brazil to the San Jorge Gulf, Santa Cruz, Argentina. It inhabits the continental shelf at depths of 13-160 m. It is caught in commercial and artisanal demersal trawl fisheries, which are intense in parts of its range, and is typically discarded dead where caught. This species is still caught commonly in fisheries despite a long history of fishing pressure and it is not suspected to be close to reaching the population reduction thresholds. Therefore, the Zipper Sandskate is assessed as Least Concern.